Effects of adaptation to intermittent high altitude hypoxia on ischemic ventricular arrhythmias in rats - Asemu, G; Neckár, J; Szárszoi, O; Papousek, F; Ostádal, B; Kolar, F (Physiological research, 2000)
We compared the effects of adaptation to intermittent high altitude (IHA) hypoxia of various degree and duration on ischemia-induced ventricular arrhythmias in rats. The animals were exposed to either relatively moderate hypoxia of 5000 m (4 or 8 h/day, 2-3 or 5-6 weeks) or severe hypoxia of 7000 m (8 h/day, 5-6 weeks). Ventricular arrhythmias induced by coronary artery occlusion were assessed in isolated buffer-perfused hearts or open-chest animals. In the isolated hearts, both antiarrhythmic and proarrhythmic effects were demonstrated depending on the degree and duration of hypoxic exposure. Whereas the adaptation to 5000 m for 4 h/day decreased the total number of premature ventricular complexes (PVCs), extending the daily exposure to 8 h and/or increasing the altitude to 7000 m led to opposite effects. On the contrary, the open-chest rats adapted to IHA hypoxia exhibited an increased tolerance to arrhythmias that was even more pronounced at the higher altitude. The distribution of PVCs over the ischemic period was not altered by any protocol of adaptation. It may be concluded that adaptation to IHA hypoxia is associated with enhanced tolerance of the rat heart to ischemic arrhythmias unless its severity exceeds a certain upper limit. The opposite effects of moderate and severe hypoxia on the isolated hearts cannot be explained by differences in the occluded zone size, heart rate or degree of myocardial fibrosis. The proarrhythmic effect of severe hypoxia may be related to a moderate left ventricular hypertrophy (27 %), which was present in rats adapted to 7000 m but not in those adapted to 5000 m. This adverse effect can be overcome by an unknown protective mechanism(s) that is absent in the isolated hearts.
Keywords: velikost orgánu; nadmořská výška; Male; Rats, Wistar; Organ Size; srdce; Adaptation, Physiological; techniky in vitro; Hypoxia; Myocardium; mužské pohlaví; potkani Wistar; fyziologická adaptace; Myocardial Ischemia; Severity of Illness Index; komorové extrasystoly; hydroxyprolin; Body Weight; krysa rodu Rattus; Hydroxyproline; Animals; Altitude; zvířata; Rats; Ventricular Premature Complexes; ischemická choroba srdeční; stupeň závažnosti nemoci; Heart; tělesná hmotnost; hypoxie; myokard; In Vitro Techniques